Keabsahan Perjanjian Kredit Dengan Fitur Shopee Paylater Pada Aplikasi Shopee : (Studi Perbandingan Kuh Perdata Dan Hukum Islam) - Elinda Sari; Rahmawati Kusuma (Private Law, 2022)
This study aims is to know and to analyze debt agreement legal concept in the view of KUHPerdata and Islamic Law, and how is the concept of debt agreement by using Shopeepaylater in Shoppe app according to KUHPerdata and Islamic Law. This research applied normative legal research and statute and comparative approaches. result of this study shows that, according to KUHPerdata, credit agreement on the using shopeepaylater has been comply with all legal requirements in the KUHPedata and related law sources such as implementing regulations from Shopee paylater, thus in the perspective of KUHPerdata shopee paylater agreement is legit. However, in the perspective of Islamic Law shopeepay later is not valid because it is violates the sharia principle, which is it has usury element with 2,95% of interest and every added value which agreed in the agreement conclusion or contract, then it is usury or “riba”, thus shopee pay later in the perspective of Islamic Law is invalid.